Analisis Penempatan Dan Kondisi Alat Pemadam Api Ringan (Apar) Dalam Sistem Penanggulangan Dan Pemadaman Kebakaran Di Pekerjaan Panas Pt X Di Area Terbuka - Luqman Ashari; Syariful Hakim Al Faruq; Naufal Nail (JURNAL ILMIAH RESEARCH AND DEVELOPMENT STUDENT, 2023)
This study discusses the 2) fire 1) emergency response system at PT X, a sub-contractor in the Gresik area. Most of the sub-contractor's work is carried out in 3) open areas, especially in the NPK fertilizer area. One of the jobs done is hot work. An important aspect of hot work is handling any 2) fire hazards that can arise. The potential for 2) fire and explosion hazards caused by incorrect operating procedures is a serious threat that must be taken seriously in the work environment. If not managed, handled and managed properly, it can cause major disasters and significant financial losses. Based on a survey conducted at PT X, the sub-contractor already has an 1) emergency response system, such as a 4) fire watcher, 5) emergency response procedures, and the use of a 6) light fire extinguisher (APAR). However, the placement of APAR has not been carried out properly when the work is carried out in an open area